Influence of agrophysical and agrochemical properties of fused and leached chernozemes on the yield of agricultural crops - Y. A. Chumachenko; N. I. Mamsirov; A. K. Shkhapatsev (Новые технологии)
The article presents the results of an assessment of the state of agrophysical and agrochemical properties of fused and leached chernozems and determination of the most promising crops for cultivation on these soil subtypes. It has been revealed that the leached chernozems are the most optimal soils of the Republic of Adygea for the cultivation of field crops. They have a large thickness of the humus layer, a loose and slightly densified composition along the profile, a favorable ratio of all types of porosity and absorbed bases, accessibility of basic nutrients, optimal reaction of the medium, which makes it possible to cultivate most of the crops on these soils.